1973
DOI: 10.1271/bbb1961.37.2295
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilities of Yeasts to Yeast Cell Wall Lytic Enzyme of Arthrobaeter luteus

Abstract: The susceptibilities of various strains of yeast to a yeast cell wall lytic enzyme produced by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Many yeast species have a cell wall similar to that of S. cerevisiae and contain glycoproteins with a structural role similar to that of the mannoprotein in S. cerevisiae (4,14). on September 1, 2020 by guest http://aem.asm.org/…”
Section: Discussionmentioning
confidence: 99%
“…Many yeast species have a cell wall similar to that of S. cerevisiae and contain glycoproteins with a structural role similar to that of the mannoprotein in S. cerevisiae (4,14). on September 1, 2020 by guest http://aem.asm.org/…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be the result of supplementation of nutrients and/or the improvement of digestibility characteristics. In addition, it has been demonstrated that the structural organization, composition and digestibility of the yeast cell wall differ considerably with species (Bartnicki-Garcia 1968; Kreger-Van Rij and Veenhuis 197 1) and strain (Rost and Venner 1965;Kaneko et al 1973). Finally, susceptibility to enzymatic degradation may also be influenced by age of the culture and by medium com-position (Killick 1971;Kratky et al 1975) or various other culture conditions (Kaneko et al 1973).…”
Section: Oiwllidclinked Proteinmentioning
confidence: 99%
“…The present communication reports such a study on S. cereLisiae NCYC366, a strain that is particularly susceptible to digestion with /Bglucanase (1,8). The study used, as a source of ,8-glucanase, Zymolyase-5000, a preparation obtained from filtrates of Arthrobacter luteus cultures (11,13). Zymolyase is reported to be free from ,B-(1--2), 13-(1--*4), and ,B-(1--6) glucanases and phosphomannanase (12).…”
mentioning
confidence: 99%